Socio-psychological portrait of a modern teenager (sociological survey analysis) - S. E. Titor (Вестник университета, 2023)
Adolescence is traditionally attributed to the period of life from 11–12 to 14–15 years. The main contradiction of adolescence is that a teenager wants to be an adult, wants others to treat him as an adult, however, he himself does not feel genuine adulthood. These problems are often provoked by negative information from the internet environment. As part of the study of destructive information environment impact on minors, a sociological study was conducted. It was conducted by anonymous survey of adolescents of various social groups. According to the results of a sociological survey, the author drew a portrait of a modern teenager, identified the problems of the external environment in which he (she) is brought up.